2021
DOI: 10.1109/lmwc.2020.3040101
|View full text |Cite
|
Sign up to set email alerts
|

An Upgraded Dual-Band Digital Predistorter Model for Power Amplifiers Linearization

Abstract: Digital predistortion (DPD) based on Volterra models is commonly employed to counteract nonlinear distortion of power amplifiers. However, when concurrent dual-band signals are transmitted, two-dimensional DPD models are required. In this work an upgrading of a standard dual-band model is proposed and justified using multinomial theorem. The linearization performance of the current proposal has been compared to the unextended model. 5G New Radio signals have been generated to compose a dual-band signal, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Neural Network-Based Model Waveform Processing at Transmission and Observation Path [67], [81], [89]- [103] [110]- [120], [122], [123] [67], [75], [82]- [88] DAC and ADC nonidealities [29], [130], [133]- [141] RF Sub-Components Effects [130]- [132], [142], [145] [130], [131] Amplitude-Compensated Phase Shifter [78], [79], [148]- [155], [157], [158] Phase-Compensated and Low-Noise Variable Gain Amplifier [44], [149], [159]- [169] SVM-Based Model better output performance. Since the invention of wireless communication, the linearity of transmitting signals hold paramount importance [73], [74].…”
Section: Baseband Waveform Processing Volterra Series-based Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Neural Network-Based Model Waveform Processing at Transmission and Observation Path [67], [81], [89]- [103] [110]- [120], [122], [123] [67], [75], [82]- [88] DAC and ADC nonidealities [29], [130], [133]- [141] RF Sub-Components Effects [130]- [132], [142], [145] [130], [131] Amplitude-Compensated Phase Shifter [78], [79], [148]- [155], [157], [158] Phase-Compensated and Low-Noise Variable Gain Amplifier [44], [149], [159]- [169] SVM-Based Model better output performance. Since the invention of wireless communication, the linearity of transmitting signals hold paramount importance [73], [74].…”
Section: Baseband Waveform Processing Volterra Series-based Modelmentioning
confidence: 99%
“…Interestingly, the nonlinearity modeling is also evolved with every mobile generation, based on the necessary distortion (ACPR) levels assisted by the governing authorities [77]. From the linearization of standalone TX elements to the mMIMO TRX compounds [49] about maintaining the uniform phase setting of the desired beam through analog circuitry [44], [78], [79] or squeezing the IB nonlinear distortion via DPD assembly [80], [81] intimates the successful deployments of PD schemes from recent times.…”
Section: Baseband Waveform Processing Volterra Series-based Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper uses the power series model as the nonlinear mathematical model of the power amplifier. In the literature (Dalbah et al , 2020; Wang et al , 2019c; Pérez-Hernández et al , 2021), the baseband equivalent input and output relationship are shown in equation (1): where i denotes the i-th wireless communication transmit link. To make a clarification here, the power amplifier because it is at the transmitting end of the subsystem, i can denote both the i-th subsystem and the transmitting link of the i - th subsystem.…”
Section: Establish-related Mathematical Modelsmentioning
confidence: 99%
“…This paper uses the power series model as the nonlinear mathematical model of the power amplifier. In the literature (Dalbah et al, 2020;Wang et al, 2019c;Pérez-Hern andez et al, 2021), the baseband equivalent input and output relationship are shown in equation ( 1):…”
Section: Establish-related Mathematical Modelsmentioning
confidence: 99%